Drought variability and land degradation in the Amazon River basin - Paredes-Trejo, Franklin; Barbosa, Humberto; Giovannettone, Jason; Kumar, T. V. Lakshmi; Kumar Thakur, Manoj; de Oliveira Buriti, Catarina (Frontiers in Earth Science, 2022)
The Amazon River Basin (ARB) plays an essential role in global climate regulation. Recent studies have revealed signs of increasing drought conditions in different parts of the basin. Although human activities have degraded large areas, little work has been done to assess whether prolonged drought may exacerbate land degradation. Among different methods for monitoring land degradation, the Sustainable Development Goal (SDG) indicator 15.3.1 adopted by the United Nations Convention to Combat Desertification (UNCCD) allows a comprehensive assessment of the impacts of land degradation due to its multi-factor nature and scalability. The aims of this study are twofold: (1) to assess the status of land degradation using the SDG indicator 15.3.1 from 2001 to 2020 in the ARB; and (2) to explore the relationship between the detectability of land degradation using the UNCCD approach and long-term drought severity. The Standardized Precipitation Index (SPI), Standardized Precipitation-Evapotranspiration Index (SPEI), and self-calibrating Palmer Drought Severity Index (scPDSI) were used as drought indices. The results revealed 757,704 km2 (12.67% of the basin) as degraded land, which was reflected by a downward trend in land productivity dynamics followed by the combined downward trend in land productivity, Soil Organic Carbon (SOC) degradation, and land cover degradation. The largest land degradation hotspot was identified along the southwestern boundary of the Amazon River Basin. Furthermore, there was strong evidence that the detection of land degradation through SDG indicator 15.3.1 is sensitive to long-term drought, which was particularly true when applied to rainfed croplands.